Exploring electrochemical mechanisms for clindamycin degradation targeted at the efficient treatment of contaminated water - Faria, Julia; Santacruz, William; De Mello, Rodrigo [UNESP]; Boldrin, Maria Valnice [UNESP]; Motheo, Artur J. (Elsevier, 2024)
Numerous studies reveal pollutants like clindamycin (CLD) in the environment, posing environmental and health risks. Conventional water treatment methods are ineffective at removing these contaminants, typically found in low concentrations. An innovative treatment approach is introduced through pre-concentration via adsorption, which is highly efficient, energy-saving, and reusable. The innovation uses solvents like methanol or ethanol to desorb pollutants, creating concentrated CLD solutions for more effective electrochemical degradation than conventional methods. Thus, this study explores, for the first time, the behavior of CLD electro-oxidation in different media—water, methanol, and ethanol—using a Dimensionally Stable Anode (DSA®-Cl₂). The study reveals distinct degradation mechanisms and offers new insights into solvent-assisted electrochemical treatments. After 30 min of electrolysis, all the current densities evaluated promoted significant degradation, ranging from 90 to 92%. The energy consumption was 2.9 Wh m⁻³ per percentage point at current densities of 2 and 3.5 mA cm⁻2. This demonstrates that using higher current densities over shorter electrolysis times is feasible, achieving removal rates of approximately 90%.The performance of chloride-based electrolytes was superior to that of sulfate-based electrolytes due to the ability of DSA®-Cl2 electrodes to generate reactive chlorine species more efficiently. A higher concentration of supporting electrolytes initially improved CLD removal, but no significant changes were observed after 1 h. Neutral pH conditions optimized CLD degradation, achieving up to 91% removal. Higher pollutant concentrations were associated with lower kinetic constants and decreased removal percentages. Methanol and ethanol enhanced removal rates to 98.3% and 92.3%, respectively, by generating oxidizing species such as methoxy, hydroxymethyl, and ethoxy radicals. The degradation by-products differed across the three media, with each solvent exhibiting distinct oxidation mechanisms. These findings highlight the potential of using methanol or ethanol as an electrolytic medium with efficiency comparable to water.
Keywords: Degradation; Electrochemical oxidation; Preconcentration; Water treatment